Divergent complement system activation in two clinically distinct murine models of multiple sclerosis - Linzey, Michael; DiSano, Krista; Welsh, Nora; Pachner, Andrew; Gilli, Francesca (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is a neurological disease featuring neuroinflammation and neurodegeneration in young adults. So far, most research has focused on the peripheral immune system, which appears to be the driver of acute relapses. Concurrently, the mechanisms underlying neurodegeneration in the progressive forms of the disease remain unclear. The complement system, a molecular component of innate immunity, has been recently implicated in several neurological disorders, including MS. However, it is still unknown if the complement proteins detected in the central nervous system (CNS) are actively involved in perpetuating chronic inflammation and neurodegeneration. To address this knowledge gap, we compared two clinically distinct mouse models of MS: 1) proteolipid protein (PLP)-induced experimental autoimmune encephalomyelitis (rEAE) resembling a relapsing-remitting disease course, and 2) Theiler’s murine encephalomyelitis virus-induced demyelinating disease (TMEV-IDD) resembling a progressive disease. Real-time PCR was performed in the spinal cord of rEAE mice, TMEV-IDD mice and age-matched sham controls to quantify gene expression for a broad range of complement components. In both experimental models, we found significantly increased expression of complement factors, such as C1q, C3, CfB, and C3aR. We showed that the complement system, specifically the classical complement pathway, was associated with TMEV-IDD pathogenesis, as the expression of C1q, C3, and C3aR1 were all significantly correlated to a worse disease outcome (all P0.0168). In line with this finding, C1q and C3 deposition was observed in the spinal cord of TMEV-IDD mice. Furthermore, C1q deposition was detected in spinal cord regions characterized by inflammation, demyelination, and axonal damage. Conversely, activation of the classical complement cascade seemed to result in protection from rEAE (C1q: P=0.0307). Interestingly, the alternative pathway related to a worse disease outcome in rEAE (CFb: P=0.0006). Overall, these results indicate potential divergent roles for the complement system in MS. The chronic-progressive disease form is more reliant on the activation of the classic complement pathway, while protecting from acute relapses. Conversely, relapsing MS appears more likely affected by the alternative pathway. Understanding the functions of the complement system in MS is critical and can lead to better, more targeted therapies in the future.